PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN PLAYGROUP DI DESA PAKISBARU, KECAMATAN NAWANGAN KABUPATEN PACITAN - SUBROTO , SUBROTO (2011)
The purposes of this research is to describe The Society's Roles in Developing Preschool Education in Pakisbaru Village, Nawangan District of Pacitan Residence, especially as educator, motivator, and facilitator. This is a qualitative research with an ethnography of educational design. This research is taken place Preschool Education in Pakisbaru Village, Nawangan District of Pacitan Residence. Method of collecting data are using 1) in-depth interview with the informants, such as the educational owner, the educational workers, and some of the societies 2) observations by visiting continuously to the location and take attention to the situations that factually according with the necessary data of focus and sub focus of the research, 3) collecting another documents which related with focus and sub focus of the research. Data validity is tested by using triangulations technique, such informants triangulation and method triangulation. The result of this research are 1) some of the societies give educatioanal and training to the educational workers and the educational owner prepare the written references, so they can learn much better 2) the educational workers are hoped to fulfil the academic qualification and receive the compensation that collecting by the educational owner 3) the societies have high concern in developing preschool education by giving financial support to the school, including to the parents who do not mind to pay the charge in each month. The suggestion of this research are 1) the educational workers should fulfil the academic qualification according with the system of national education 2) the department of education should give the primary priority in developing preschool education 3) the societies should participate in developing preschool education 4) the other researchers should expand the result of this research with another reference.